Goodbye, vitamin : a novel - Khong, Rachel, 1985- (Henry Holt and Company, 2017)
"Incredibly poignant . . . Rachel Khong's first novel sneaks up on you -- just like life . . . and heartbreak. And love."--Miranda July A few days after Christmas in a small suburb outside of L.A., pairs of a man's pants hang from the trees. The pants belong to Howard Young, a prominent history professor, recently diagnosed with Alzheimer's disease. Howard's wife, Annie, summons their daughter, Ruth. Freshly disengaged from her fiance and still broken up about it, feeling that life has not turned out quite the way she planned, thirty-year- old Ruth quits her job, and arrives home to find her parents' situation worse than she'd realized. Her father is erratically lucid and her mother, a devoted and creative cook, sees the sources of memory loss in every pot and pan. But as Howard's condition intensifies, the comedy in Ruth's situation takes hold, gently transforming her grief. She throws herself into caretaking: cooking dementia-fighting meals (a feast of jellyfish!), researching supplements, anything toreignite her father's once-notable memory. And when the university finally lets Howard go, Ruth and one of her father's handsome former students take their efforts to help Howard one step too far. Told in captivating glimpses and drawn from a deep well ofinsight, humor, and unexpected tenderness, Goodbye, Vitamin pilots through the loss, love, and absurdity of finding a one's footing in this life"--